Huperzine A as a neuroprotective and antiepileptic drug: a review of preclinical research. (2nd June 2016) - Damar, U.; Gersner, R.; Johnstone, J. T.; Schachter, S.; Rotenberg, A.
ABSTRACT: Huperzine A (HupA) is an acetylcholinesterase (AChE) inhibitor extracted from Huperzia Serrata, a firmoss, which has been used for various diseases in traditional Chinese medicine for fever and inflammation. More recently, it has been used in Alzheimer's disease and other forms of dementia with a presumed mechanism of action via central nicotinic and muscarinic receptors. HupA is marketed as a dietary supplement in the U.S. This article reviews newly proposed neuroprotective and anticonvulsant HupA properties based on animal studies. HupA exerts its effects mainly via α7nAChRs and α4β2nAChRs, thereby producing a potent anti-inflammatory response by decreasing IL-1β, TNF-α protein expression, and suppressing transcriptional activation of NF-κB signaling. Thus, it provides protection from excitotoxicity and neuronal death as well as increase in GABAergic transmission associated with anticonvulsant activity.